(untitled) (Socio-economic relations in the digital society, 2019)
In the paper the problem of economic education of children and youth in Galicia XIX – early XX century: economic, cultural and educational background.The most significant contribution to the Ukrainian national revival on the basis of the professional schools have made society “Enlightenment”, “Native School”, “Audit Union of Ukrainian Cooperatives”, “International trade”, “Farmer”, “Maslosoyuz” and others. They have a common goal but at the same time, signifi cant differences in the content and structure of vocational training, organizational and pedagogical forms management. The methodological bases of social and economic conditions, the regulatory framework of their functioning at different stages of history had its own peculiarities. Objective circumstances at the current stage require the use of theoretical and organizational achievements of predecessors in sphere cooperation in the educational process and the process of creating a statehood, which is based on a dynamic economy.